Microwave and optical waveguide analysis by the finite element method - Fernandez, F. Anibal (Electronic & electrical engineering research studies. Optoelectronics series, 1996)
A very efficient and robust method which gives a complete description of the spectrum of microwaves and optical waveguides and waveguide-based devices, including propagating, evanescent and radiating modes, is presented.The method can be implemented on a personal computer and in a form which is not dependent on the specific problem. Full details of the mathematical formulation and its finite element implementation are given together with a variety of examples. The finite element formulation presented in this book is based on transverse fields for maximum economy and is free from spurious solutions. Maximum efficiency is also achieved by solving directly for the propagation constant and taking full advantage of the sparsity of the matrices involved.